2018
DOI: 10.1111/jcmm.13948
|View full text |Cite
|
Sign up to set email alerts
|

5,2′‐dibromo‐2,4′,5′‐trihydroxydiphenylmethanone attenuates LPS‐induced inflammation and ROS production in EA.hy926 cells via HMBOX1 induction

Abstract: Inflammation and reactive oxygen species (ROS) are important factors in the pathogenesis of atherosclerosis (AS). 5,2′‐dibromo‐2,4′,5′‐trihydroxydiphenylmethanone (TDD), possess anti‐atherogenic properties; however, its underlying mechanism of action remains unclear. Therefore, we sought to understand the therapeutic molecular mechanism of TDD in inflammatory response and oxidative stress in EA.hy926 cells. Microarray analysis revealed that the expression of homeobox containing 1 (HMBOX1) was dramatically upre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…It has been reported that NF-κB is released into the cell nucleus and binds to genes to initiate transcription leading to inflammation, oxidative stress, and apoptosis after being stimulated by some external factors. [45][46][47] NO is synthesized by iNOS, COX-2. In terms of some metal iron induced inflammatory response, NF-κB controls the expressions of NO to reduce inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that NF-κB is released into the cell nucleus and binds to genes to initiate transcription leading to inflammation, oxidative stress, and apoptosis after being stimulated by some external factors. [45][46][47] NO is synthesized by iNOS, COX-2. In terms of some metal iron induced inflammatory response, NF-κB controls the expressions of NO to reduce inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%
“…The present study found also that increased HMBOX1 inhibited NF-κB activation in hPDLSCs in response to LPS. In addition to the potential involvement of NF-κB in the regulatory role of HMBOX1 in response to LPS, a previous study also showed that 5'AMP-activated protein kinase mediates the regulation of HMBOX1, which is associated with inflammation after EA.hy926 cells were subjected to LPS stimulation (9). Additionally, HMBOX1 has been reported to be involved in cancer progression in an AKT-dependent manner, including osteosarcoma, lung cancer and liver cancer (23)(24)(25).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the NF-κB signaling pathway was found to upregulate the expression of CXCL10 in COMM domain-containing protein 7-treated hepatocellular carcinoma cells (18). Aldo-keto reductase family 1 member C2 was also discovered to exert potent anti-inflammatory and antioxidant effects by inhibiting NF-κB activity downstream of HMBOX1 activation in an atherosclerosis model of LPS-induced EA.hy926 cells (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, overexpression of miRNA-124 in MSCs was shown to drive their differentiation into neurons and promote functional recovery of spinal rats [ 92 ]. However, another possible mechanism for this recovery could be the decrease in the number of apoptotic cells; miRNA-124 blocks the mitochondrial pathway of apoptosis in vivo [ 93 ] and LPS-induced apoptosis in vitro [ 94 ].…”
Section: Keeping a Balance Between Neuronal Apoptosis And Autophagymentioning
confidence: 99%